Jasmonate-Mediated Induced Volatiles in the American Cranberry, Vaccinium macrocarpon: From Gene Expression to Organismal Interactions - Rodriguez-Saona, Cesar; Polashock, James; Malo, Edi (Frontiers in Plant Science, 2013)
Jasmonates, i.e., jasmonic acid (JA) and methyl jasmonate (MeJA), are signaling hormones that regulate a large number of defense responses in plants which in turn affect the plants’ interactions with herbivores and their natural enemies. Here, we investigated the effect of jasmonates on the emission of volatiles in the American cranberry, Vaccinium macrocarpon, at different levels of biological organization from gene expression to organismal interactions. At the molecular level, four genes (BCS, LLS, NER1, and TPS21) responded dramatically to gypsy moth larval feeding, MeJA, and mechanical wounding, but to different degrees. The most dramatic changes in expression of BCS and TPS21 (genes in the sesquiterpenoid pathway) were when treated with MeJA. Gypsy moth larval feeding and MeJA treated plants also had dramatically elevated expression of LLS and NER1 (genes in the monoterpene and homoterpene biosynthesis pathways, respectively). At the biochemical level, MeJA induced a complex blend of monoterpene and sesquiterpene compounds that differed from gypsy moth and mechanical damage, and followed a diurnal pattern of emission. At the organismal level, numbers of Sparganothis sulfureana moths were lower while numbers of parasitic wasps were higher on sticky traps near MeJA-treated cranberry plants than those near untreated plants. Out of 11 leaf volatiles tested, (Z)-3-hexenyl acetate, linalool, and linalool oxide elicited strong antennal (EAG) responses from S. sulfureana, whereas sesquiterpenes elicited weak EAG responses. In addition, mortality of S. sulfureana larvae increased by about 43% in JA-treated cranberry plants as compared with untreated plants, indicating a relationship among adult preference, antennal sensitivity to plant odors, and offspring performance. This study highlights the role of the jasmonate-dependent defensive pathway in the emissions of herbivore-induced volatiles in cranberries and its importance in multi-trophic level interactions.